If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-3)=5x-(x+21)
We move all terms to the left:
5(x-3)-(5x-(x+21))=0
We multiply parentheses
5x-(5x-(x+21))-15=0
We calculate terms in parentheses: -(5x-(x+21)), so:We get rid of parentheses
5x-(x+21)
We get rid of parentheses
5x-x-21
We add all the numbers together, and all the variables
4x-21
Back to the equation:
-(4x-21)
5x-4x+21-15=0
We add all the numbers together, and all the variables
x+6=0
We move all terms containing x to the left, all other terms to the right
x=-6
| y+1,5=5,5 | | 4z/9+6=9 | | 2/3p+5=10 | | 0=x2+7x-18 | | (17+y)y=89 | | 9+18x=5(9x+11)+x | | 5+17x=3(8x+22)-x | | 11(15x+18)=-38(x-3) | | (-4)=2x^2+5x+3 | | 12(6x+4)=-12(x-3) | | F(4)=2x^2+5x+3 | | 20(12x+4)=16(x-2) | | 8(15x-6)=32(x+3) | | 2n²=200 | | 2(14x-21)=37(x+4) | | X2-12x+20=0 | | 16(-7x-11)=14(x+5) | | X^2=8x-22 | | 60=2x2+14x+24 | | (7n)^n=7^7^7 | | 3-(2x-1)-2x=5 | | 20(-10x+8)=-3(x-3) | | (7x-3)^2-(9)=0 | | 9^x-4×3^x+3=0 | | 2+7x=3(19x+24)+x | | 4k−6=-2k−16−24k-6=-2k-16-24k−6=-2k−184k-6=-2k-184k=-2k | | 5+4m=68.96 | | 6x+(-12)=2x+36 | | 20-8x=15+1x | | 4m+5=68.96 | | 3^х+1×3^x-2=3^3 | | 17x+(-14)=9 |